2020
DOI: 10.3390/ijms21124540
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Biology of Human Interstitial Cells of Cajal in Gastrointestinal Motility

Abstract: Millions of patients worldwide suffer from gastrointestinal (GI) motility disorders such as gastroparesis. These disorders typically include debilitating symptoms, such as chronic nausea and vomiting. As no cures are currently available, clinical care is limited to symptom management, while the underlying causes of impaired GI motility remain unaddressed. The efficient movement of contents through the GI tract is facilitated by peristalsis. These rhythmic slow waves of GI muscle contraction are mediated by sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 109 publications
(173 reference statements)
1
66
0
1
Order By: Relevance
“…ICCs act as pacemakers of gastrointestinal motility [ 19 ]. Reduction, injury, or loss of function of gastrointestinal tract ICCs may be associated with impaired gastrointestinal motility [ 20 ]. ICCs undergo apoptosis over time, and maintenance of ICCs networks is required for adequate regeneration of healthy tissues [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICCs act as pacemakers of gastrointestinal motility [ 19 ]. Reduction, injury, or loss of function of gastrointestinal tract ICCs may be associated with impaired gastrointestinal motility [ 20 ]. ICCs undergo apoptosis over time, and maintenance of ICCs networks is required for adequate regeneration of healthy tissues [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial cells of Cajal (ICCs) were first described in the gastrointestinal tract by Santiago Ramón y Cajal in 1893 [ 5 ]. In the past 100 years, studies have shown that ICCs are present in the esophagus, stomach, proximal duodenum wall, small and large bowel, ileum, appendix, and colon [ 6 ]. ICCs function in the digestive tract smooth muscle as power pacemakers, promoting gastrointestinal electrical activity, and mediating and regulating the gastrointestinal neurotransmitters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Her contribution is completed by a complementary review by Foong and al. describing the role of interstitial cells of Cajal in gastrointestinal motility [ 3 ]. Interstitial cells of Cajal are known to act like pace-makers cells, and several subtypes are described in both murine species and humans.…”
mentioning
confidence: 99%
“…Interstitial cells of Cajal are known to act like pace-makers cells, and several subtypes are described in both murine species and humans. The importance of interstitial cells of Cajal is also debated in many gastrointestinal motility disorders, and the main issue is that most studies were carried out on animal models, and one needs to elucidate if the findings can be extended to humans [ 3 ]. Additional molecular studies are needed to characterize these cells from a transcriptomic, proteomic, and electrophysiological point of view, and this involves finding a reliable source of human interstitial cells of Cajal [ 3 ].…”
mentioning
confidence: 99%
“…Moreover, the c-Kit receptor expression has been related to ICC differentiation (Sanders et al, 1999). It has also been demonstrated that c-Kit/SCF signaling is necessary for the development, differentiation, and phenotype maintenance of ICC (Foong et al, 2020). These data suggested that c-Kit receptor was a crucial protein for ICC roles in tissues.…”
Section: Discussionmentioning
confidence: 93%